Prevalence of Elder Abuse and its Related Factors among Elderly Referring to Social Security Outpatient Clinic in Yasouj, Iran - Shahab Papi; Samad Akbari; Mahshid Foroughan; Nasibeh Zanjari; Amir Mohamad Moghadasi; Zhale Zandieh (Elderly Health Journal, 2022)
Introduction: Elder abuse is a major public health concern worldwide. Considering the high prevalence of misbehavior towards the elderly, this study investigated the prevalence of elder abuse and its related factors among the elderly people in Yasouj, Iran in 2021. Methods: Using a convenience sampling method, this cross-sectional study included 299 older adults aged over 60 years referring to the Social Security Outpatient Clinic in Yasouj. To collect data, we used the Domestic Elder Abuse Questionnaire. To analyze the data, chi-square and multiple logistic regression statistical tests were used. Results: Of the participants, 55.2 % reported at least one type of misbehavior. While psychological misbehavior had the highest prevalence (41.8 %), rejection had the lowest prevalence (10.7 %). Multiple regression analysis showed that elder abuse was statistically associated with higher educational status (p = 0.002), lower economic status (p = 0.002), and single people reported a higher rate of elder abuse (p = 0.001). Conclusion: According to our results, more than half of the participants reported at least one type of elder abuse, and psychological abuse was the most common type of abuse experienced by the elderly. Since elder abuse can have serious effects on the health and well-being of the elderly, it is critical to identify the related risk factors. Furthermore, it is essential to implement screening programs to increase the awareness of the elderly and caregivers.